2021
DOI: 10.3390/brainsci11091218
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive and Omission Errors: Potential Temporal Processing Endophenotypes in ADHD

Abstract: Temporal processing (TP) is associated with functions such as perception, verbal skills, temporal perspective, and future planning, and is intercorrelated with working memory, attention, and inhibitory control, which are highly impaired in individuals with attention deficit hyperactivity disorder (ADHD). Here we evaluate TP measures as potential endophenotypes in Caribbean families ascertained from probands affected by ADHD. A total of 232 individuals were recruited and clinically evaluated using an extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…While attention is most commonly measured by accuracy of responding (Amitai & Markou, 2011; Bari et al, 2008; Robbins, 2002), our results indicate that omissions also reflect a lack of enough visual accumulation due to rats’ failure to pay attention to the curved wall during light stimulus presentation. This is particularly relevant as omission rates are an important measure on human continuous performance task (Conners, Epstein, Angold, & Klaric, 2003) and have recently been shown to represent endophenotypes in ADHD (Acosta-Lopez et al, 2021). Moreover, because response accuracy and omission reflect different aspects of attention it will be interesting in future research to see whether these two behavioral parameters rely on distinct brain regions and/or neurophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…While attention is most commonly measured by accuracy of responding (Amitai & Markou, 2011; Bari et al, 2008; Robbins, 2002), our results indicate that omissions also reflect a lack of enough visual accumulation due to rats’ failure to pay attention to the curved wall during light stimulus presentation. This is particularly relevant as omission rates are an important measure on human continuous performance task (Conners, Epstein, Angold, & Klaric, 2003) and have recently been shown to represent endophenotypes in ADHD (Acosta-Lopez et al, 2021). Moreover, because response accuracy and omission reflect different aspects of attention it will be interesting in future research to see whether these two behavioral parameters rely on distinct brain regions and/or neurophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between verbal fluency and ADHD diagnosis has been somewhat controversial. Some studies have shown no significant association between verbal fluency and ADHD (Abreu et al, 2013;Andreou & Trott, 2013;Hurks et al, 2004;Marzocchi et al, 2008), while others have demonstrated compromised performance in individuals with ADHD (Acosta-López et al, 2021;Bramham et al, 2009;Happé et al, 2006;Husain et al, 2023;Martz et al, 2022;Navarro-Soria et al, 2020;Nejati et al, 2023).…”
Section: Verbal Fluency Differences In Adhdmentioning
confidence: 99%
“…Neuropsychological tests that are characterized with higher effect sizes in patients with ADHD ( Bálint et al, 2009 ) – such as the continuous performance tests ( Conners et al, 2003 ) or the standardized neuropsychological measures, for example, Stroop task ( Golden, 1975 ), the Digit Span subtest of WAIS ( Wechsler, 1981 ) or the Wisconsin Card Sorting Test ( Heaton et al, 1993 ) – are also widely used in endophenotype investigations; however, the results are inconsistent ( Kebir and Joober, 2011 ; Faraone et al, 2014 ). A study by Acosta-López et al (2021) offers a promising approach to overcome the gap between the genotype and the phenotype, whereby applying a family-based design and using an extensive test battery of neuropsychological tasks (Stroop test, Cross-Out-Squares Test, and Trail Making Test) and also reaction time-based task paradigms (Conners’ Continuous Performance Test and Go/No-Go Tasks ( Jiménez-Figueroa et al, 2017 ; Jimenez-Figueroa et al, 2020 ); temporal processing is evaluated as a potential endophenotype in ADHD. Estimating the effect sizes for neuropsychologically based variables related to a cognitive mechanism (e.g., temporal processing) in a case–control design and the parallel estimation of the heritability of these variables within one sample group can provide variables which are likely to be relevant to both clinical (neuropsychological) and genetic perspectives.…”
Section: Introductionmentioning
confidence: 99%